Decreased long‐term graft survival in persistent biliary complications after right‐lobe living‐donor liver transplantation. Issue 1 (31st December 2019) - Ogiso, Satoshi; Kamei, Hideya; Onishi, Yasuharu; Kurata, Nobuhiko; Jobara, Kanta; Kawashima, Hiroki; Ogura, Yasuhiro
Abstract: Background: Long‐term outcomes after endoscopic treatment of post‐transplant biliary complications have not been fully understood. This study aimed to evaluate the impact of biliary complications on graft survival after right‐lobe living‐donor liver transplantation (R‐LDLT). Method: From a single‐institutional prospectively maintained database, all patients who underwent R‐LDLT between 1999 and 2017 were included. Data on patient demographics, complications, endoscopic treatment, and graft survival were retrieved for analyses. Results: Among 111 patients who underwent R‐LDLT, 33 (29.7%) developed biliary complications; of these, 19 (17.1%) were treated with biliary stenting, and the stent was removed following resolution of biliary complications in 8 of the 19 (42.1%) patients. The graft survival rate was 88.0% and 85.6% at 5‐ and 10‐year follow‐up, respectively, in patients without biliary complications, which was similar to that of the patients with resolved biliary complications (81.3% at 5‐ and 10‐year follow‐up, P = .68) but higher than that of patients having persistent (unresolved) biliary complications (61.4% and 49.1% at 5‐ and 10‐year follow‐up, respectively, P = .04). Conclusion: Post‐transplant persistent biliary complications, unresolved after endoscopic management and requiring prolonged biliary stenting, are associated with inferior graft survival. However, patients with resolved biliary complications achieve a favorable long‐term survival similar to patients without biliary complications.